Pengaruh Kombinasi Pupuk Makro Majemuk Cair dengan Pupuk NPK Terhadap Pertumbuhan dan Hasil Tanaman Jagung (Zea Mays L) - Solihin, Eso; Sudirja, Rija; Sari, Stefina Liana (Jurnal Kridatama Sains dan Teknologi, 2025)
Fertilization is a key factor in enhancing crop productivity, primarily through the provision of essential nutrients. The application of compound fertilizers containing macronutrients, either as an alternative or a complement to single-nutrient fertilizers, is expected to improve fertilization efficiency and support sustainable crop yields. This study aimed to evaluate the effect of combining macronutrient NPK compound fertilizer with single-nutrient fertilizers—nitrogen (N), phosphorus (P), and potassium (K)—on plant growth and yield, as well as to determine the optimal dosage. The experiment was conducted from December 2024 to April 2025 using a randomized complete block design (RCBD) with nine treatments and three replications. The treatments included: a control (no fertilizer), single NPK fertilizers (300 kg/ha Urea, 150 kg/ha SP-36, 100 kg/ha KCl), combinations of NPK with compound fertilizer at different dosages (½, 1, and 1½), and compound fertilizer alone (4 L/ha). The results revealed that the combination of N, P, and K with compound fertilizer significantly enhanced plant growth and yield. Among all treatments, treatment E (NPK + 1½ doses of compound fertilizer) resulted in the highest maize yield